Evaluasi Kebijakan Adopsi IPSAS di Indonesia: Sebuah Kajian Empirisme - Sari, Nia Pramita (UI Scholars Hub, 2024)
The Indonesian government's policy to reform state financial administration through the adoption of IPSAS in Indonesia has drawn controversy among accounting academics. This study evaluates the policy from an empiricist perspective in the epistemology of the philosophy of science at the stages of formulation, evaluation, and consequences of the policy. The results of the analysis show that the formulation and evaluation stages that are not based on the principle of empiricism that emphasizes observable evidence in the formation of ideas and scientific studies cause various obstacles in the implementation process and ultimately have negative consequences for society. This article presents recommendations that can be made to improve future policies.